KONTRAVENSI MASYARAKAT TERHADAP PERUBAHAN NAMA BANDARA INTERNASIONAL LOMBOK DI KABUPATEN LOMBOK TENGAH - ASRI SOPIANTI (Universitas Hamzanwadi, 2019)
Contravention of changing the name of Lombok International Airport in Sukaraja Village is still being rejected both individually and in groups. At that time, there was a polemic in the people of West Nusa Tenggara (NTB), especially in the people of Sukaraja Village, where the Lombok International Airport operates. So that this researcher aims to find out the contravention of the Lombok International Airport Change in Sukaraja Village and to find out the basis for the community's contravention against the Change in International Airport. This research uses a qualitative approach with descriptive research type. Descriptive research is a series of activities in order to obtain data or information that is real, and to provide a thorough and in-depth understanding. The data collection used was observation, interviews, and documentation. Furthermore, the data used were qualitative data analysis through the stages of data reduction, data presentation, and conclusion drawing. From the findings in the field, researchers can report in Sukaraja Village to the community's contravention of the change in the name of the Lombok International Airport (BIL), namely in the community response the name of the airport is still conflicting and has not fully accepted the change in the name of Lombok International Airport, because of individual or group interests, among them concerns (mass organizations), the group members' disagreements about the existing community goals initially served as a common guideline and the rules in the group lived by its members contradict each other.